2020
DOI: 10.21203/rs.2.21135/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription Factors and microRNA Genes Regulatory Network Construction Under Drought Stress in Sesame (Sesamum indicum L.)

Abstract: Background: Drought is one of the most common environmental stresses affecting crops yield and quality. Sesame is an important oilseed crop that most likely faces drought during its growth due to growing in semi-arid and arid areas. Plants responses to drought controlled by regulatory mechanisms. Despite this importance, there is little information about Sesame regulatory mechanisms against drought stress. Results: 458 drought-related genes were identified using comprehensive RNA-seq data analysis of two susce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
(111 reference statements)
1
1
0
Order By: Relevance
“…Additionally, pectate lyase 18 (LOC21400038) expression level was significantly lower (Figure 12G). Pectate lyase is involved in cell wall modification, and formation of root structures and downregulation of pectase layse response to drought stress has been recently reported, which agrees with our work [64]. Finally, though the level of the uncharacterized gene (LOC21387341) expression in the drought stress was less than in control, its expression level somehow increased appreciably.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, pectate lyase 18 (LOC21400038) expression level was significantly lower (Figure 12G). Pectate lyase is involved in cell wall modification, and formation of root structures and downregulation of pectase layse response to drought stress has been recently reported, which agrees with our work [64]. Finally, though the level of the uncharacterized gene (LOC21387341) expression in the drought stress was less than in control, its expression level somehow increased appreciably.…”
Section: Discussionsupporting
confidence: 92%
“…The CPRF2 protein which is a member of bZIP TF family is related to the regulation system controlling chalcone syn-thase through hormone control or light-induction. The overexpression of such gene under drought stress have been reported in Sesame [55], which could be due it is known relation in flower development [56]. The ORR6 gene is related to cytokinin signaling, and recently it has been reported that it could be downregulated in some salt-tolerant maize inbred line [57].…”
Section: Alsamman Et Al 2021mentioning
confidence: 99%